2022
DOI: 10.1002/jmv.28383
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 infection activates CREB/CBP in cellular cyclic AMP‐dependent pathways

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has caused a global coronavirus disease 2019 (COVID‐19) pandemic that has affected the lives of billions of individuals. However, the host‐virus interactions still need further investigation to reveal the underling mechanism of SARS‐CoV‐2 pathogenesis. Here, transcriptomics analysis of SARS‐CoV‐2 infection highlighted possible correlation between host‐associated signaling pathway and virus. In detail, cAMP‐protein kinase (PKA) pathway has an essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Each of these spiRNAs will reliably block both synthesis of the protein encoded by the spiRNAs target and gRNA replication. The effectiveness of spiRNAs is expected to be the same as in many experiments using synthetic interfering siRNA molecules [49][50][51][52][53].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Each of these spiRNAs will reliably block both synthesis of the protein encoded by the spiRNAs target and gRNA replication. The effectiveness of spiRNAs is expected to be the same as in many experiments using synthetic interfering siRNA molecules [49][50][51][52][53].…”
Section: Resultsmentioning
confidence: 95%
“…Such a large value of ΔG is also associated with the length of piRNAs from 28 nt to 31 nt. These spiRNAs, fully complementary to gRNAs, are identical in function to widely used siRNAs that cause inhibition of viral RNA protein synthesis [49][50][51][52][53]. These examples demonstrate the possibility of creating drugs that suppress the reproduction of coronavirus in human cells.…”
Section: Resultsmentioning
confidence: 96%
“…Each of these spiRNAs will reliably block both the synthesis of the protein encoded by the spiRNAs target and gRNA replication. The effectiveness of spiRNAs is expected to be the same as in many experiments using synthetic interfering siRNA molecules [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 97%
“…Such large values of ΔG are also associated with the length of piRNAs from 28 nt to 31 nt. These spiRNAs, fully complementary to gRNAs, are identical in function to widely used siRNAs that cause inhibition of viral RNA protein synthesis [ 51 , 52 , 53 ]. These examples demonstrate the possibility of creating drugs that suppress the reproduction of coronavirus in human cells.…”
Section: Resultsmentioning
confidence: 99%
“…As an important second messenger, cAMP is involved in many different cellular activities, acting through cAMP-dependent effectors such as protein kinase A (PKA) and exchange proteins directly activated by cAMP ( 32 ). Yang et al ( 33 ) found that the cAMP-PKA pathway was involved in the SARS-CoV-2 infection process and induced the activation of the downstream transcription factor cAMP response element-binding protein (CREB). In studies of neuropsychiatric disorders such as TS, abnormalities in second messengers are often found.…”
Section: Discussionmentioning
confidence: 99%